A study of share investment by CPF members - Lee, Gek Lin (2015)
Currently, the bull run in the stock market has attracted many Singaporeans to invest in shares. This increase in the number of investors is also due to the fact that the government is Singaporeans to have a stake actively encouraging in government-linked companies. One such example is the offering of Singapore Telecoms shares at a concessionary price. On top of this, the Central Provident Fund Board (CPF) has also revised the existing CPF Investment Scheme and introduced the Enhanced Investment Scheme. Therefore there is a need to study the success of the existing CPF Investment Scheme. The bigger amount of withdrawals for investment and the benefits the investors have received from the existing Scheme indicate that it has succeeded. Newspaper reviews, data collection from the CPF Resource Centre and a questionnaire survey on a sample size of 150 were conducted for this study.